2013
DOI: 10.1515/lp-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

The role of rhythm class, speaking rate, and F0 in language discrimination

Abstract: Abstract:The division of languages into stress-, syllable-, and mora-timing is said to be supported by experiments showing that languages are discriminated only if they belong to different rhythm classes, a distinction said to be reflected in the duration and variability of consonantal and vocalic intervals (timing). The role of rhythm classes in discrimination is tested here along with the alternative that discrimination is due to speaking rate and F 0 differences and is independent of rhythm class. Five AAX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…Several tempo perception studies report correlations of listeners' judgements and syllable rate measurements in the region of r=0.80 [4,5]. Research into rhythm perception highlights listeners' attention to syllable rate when judging whether utterances are rhythmically alike or distinct [6,7]. To date only one study has included segment rate measurements in the comparison [8].…”
Section: Introductionmentioning
confidence: 99%
“…Several tempo perception studies report correlations of listeners' judgements and syllable rate measurements in the region of r=0.80 [4,5]. Research into rhythm perception highlights listeners' attention to syllable rate when judging whether utterances are rhythmically alike or distinct [6,7]. To date only one study has included segment rate measurements in the comparison [8].…”
Section: Introductionmentioning
confidence: 99%
“…In all cases, values for Finnish were higher or lower than both those for French and Spanish, suggesting that no simple set of timing features can account for the observed behaviour. There is some evidence pointing to the role of f0 variation in adult discrimination tasks, though secondary to that of speech rate [20]. It should also be noted that intact natural speech was used here, as in previous discrimination experiments with fivemonth olds [17], and so segmental cuessuch as the sharply contrasting vowel inventories of French and Spanishare also available.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, adult discrimination experiments have exposed listeners to stimuli modified to eliminate segmental information and focus solely on timing (e.g., sasasa speech, created by replacing all vowels with /a/ and all consonants with /s/, but retaining the durational values of the original intervals). Initial results suggested that adult discrimination was also governed by categorical rhythm class distinctions [18], but this interpretation was challenged by studies showing within-class and within-language discrimination on the basis of timing cues alone [19,20]. Such results suggest thatrather than discrete categoriesadult language discrimination relies on gradient variation along prosodic dimensions, with differences in speech rate and utterance-final lengthening shown to be particularly salient [19, see also 21 for infant discrimination between accents of a familiar language].…”
Section: Introductionmentioning
confidence: 99%
“…They have proven less successful, however, when a wider range of materials, speakers, and a larger set of languages are considered (e.g., Arvaniti, , ; Loukina, Kochanski, Rosner, Keane, & Shih, ; White & Mattys, ; Wiget, White, Schuppler, Grenon, Rauch & Mattys, 2010). Further, perception studies have failed to find consistent evidence for such classes (e.g., Arvaniti, ; Arvaniti & Rodriquez, ; White, Delle Luche, & Floccia, ).…”
Section: Rhythm and Rhythmic Timingmentioning
confidence: 99%